2019
DOI: 10.1002/elsc.201800134
|View full text |Cite
|
Sign up to set email alerts
|

Production of anti‐inflammatory compounds in Sphaeralcea angustifolia cell suspension cultivated in stirred tank bioreactor

Abstract: Sphaeralcea angustifolia is a plant used for the treatment of inflammatory processes. Scopoletin, tomentin, and sphaeralcic acid were identified as the compounds with anti‐inflammatory and immunomodulatory effects. Successful establishment of the cell culture in Erlenmeyer flasks has been reported previously. The aim of this study was to evaluate the ability of cells in suspension from S. angustifolia grown in a stirred tank bioreactor and demonstrate their capacity to produce bioactive compounds. Cells in sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Moreover, hydromechanical stress in an LM system is connected with the intensity of culture' shaking. Perez-Hernandez et al [35] examined suspension cell culture of medical plant Sphaeralcea angustifolia and revealed that cells grown with 200 rpm had the highest cell biomass and increased concentration of sphaeralcic acid. Growing cells with 100 rpm induces oxygen deficit stress, while 400 rpm negatively affects viability of cells, which was the consequence of hydrodynamic stress.…”
Section: The Effect Of Shaking On Plant Growth and Secondary Metabolimentioning
confidence: 99%
“…Moreover, hydromechanical stress in an LM system is connected with the intensity of culture' shaking. Perez-Hernandez et al [35] examined suspension cell culture of medical plant Sphaeralcea angustifolia and revealed that cells grown with 200 rpm had the highest cell biomass and increased concentration of sphaeralcic acid. Growing cells with 100 rpm induces oxygen deficit stress, while 400 rpm negatively affects viability of cells, which was the consequence of hydrodynamic stress.…”
Section: The Effect Of Shaking On Plant Growth and Secondary Metabolimentioning
confidence: 99%
“…The application of a suitable bioreactor system is crucial for plant cell cultivation in respect to biomass accumulation, cell viability and product formation (Eibl and Eibl 2008;Valdiani et al 2019). While stirred-tank reactors are routinely used for plant cell culture (Arias et al 2017;Pérez-Hernández et al 2019), the mechanical stirring poses a source of hydrodynamic stress for the plant cells, decreasing cell viability during the process (Takeda et al 1994). Alternatives without mechanical stirring are found in bubble column, airlift or some types of disposable bioreactors.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…The maximum growth of the suspended cells (19.11 g/L) was recorded 11 days after culture at 200 rpm. Sphaeralcic acid was the primary intracellular compound whose content (52.15 mg/L) was significantly higher than that reported in cells developed in Erlenmeyer flasks [ 35 ].…”
Section: Experimental Studies On S Angustifoliamentioning
confidence: 76%